Information security of intelligent vehicles communication overview, perspectives, challenges, and possible solutions - Singh, Madhusudan (Studies in computational intelligence, 2021)
This book highlights cyber-security overview, perspectives, and challenges that affect advanced Vehicular technology. It considers vehicular security issues and possible solutions, with the aim of providing secure vehicle-to-vehicle, vehicle-to-infrastructure and inside-of-vehicle communication. This book introduces vehicle cryptography mechanism including encryption and decryption approaches and cryptography algorithms such as symmetric and asymmetric cryptography, Hash functions and Digital Signature certificates for modern vehicles. It discusses cybersecurity structure and provides specific security challenges and possible solutions in Vehicular Communication such as vehicle to vehicle communication, vehicle to Infrastructure and in-vehicle communciation. It also presents key insights from security with regards to vehicles collaborative information technology. The more our vehicles become intelligent, the more we need to work on safety and security for vehicle technology. This book is of interest to automotive engineers and technical managers who want to learn about security technologies, and for those with a security background who want to learn about basic security issues in modern automotive applications.